2001
DOI: 10.1164/ajrccm.164.10.2009105
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide Decreases during Exercise-induced Bronchoconstriction in Children with Asthma

Abstract: Nitric oxide (NO) produced in the airways can be either detrimental or protective to the host. To investigate the role of NO in the pathogenesis of exercise-induced bronchoconstriction (EIB), we measured exhaled NO (ENO) after exercise challenge in 39 asthmatic and six normal children. FEV(1) and ENO were measured before and at 0, 5, 10, and 15 min after exercise performed on a treadmill for 6 min. EIB was defined as a decrease in FEV(1) of more than 15% after the exercise. Normal children (control group) did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
4
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 35 publications
7
49
4
3
Order By: Relevance
“…These observed changes last for only a short time (Ͻ5 min) postexercise, until ventilation rate returns to baseline. In contrast, exhaled NO concentration in asthma has been reported to be significantly reduced shortly after exercise (9,48,50), and the degree of EIB is significantly associated with atopy and baseline exhaled NO (37). These observations are consistent with our current findings in asthmatic and healthy subjects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These observed changes last for only a short time (Ͻ5 min) postexercise, until ventilation rate returns to baseline. In contrast, exhaled NO concentration in asthma has been reported to be significantly reduced shortly after exercise (9,48,50), and the degree of EIB is significantly associated with atopy and baseline exhaled NO (37). These observations are consistent with our current findings in asthmatic and healthy subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Mean (SD) W 50 for subjects with EIB at baseline was 206 (52) and was not impacted by the exercise challenge or bronchodilator. Mean (SD) Cpeak NO , W 50 , and A I,II values for healthy controls at baseline were 72 (32) ppb, 190 (48) ppb, and 12,822 (6,571) ppb/ml respectively, and were not impacted by the exercise challenge or bronchodilator (see Fig. 2).…”
Section: Resultsmentioning
confidence: 88%
“…Further, the fall in FeNO was small and within the coefficient of variant of the FeNO instrument used. Nevertheless, our data supports the findings of Terada et al (8) but are in contrast to Scollo et al (9) However, our study adds further novel data as neither studies examined FeNO in children with cough but without asthma. The fall in FeNO post exercise was larger in children with EIB and this difference between groups did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies found short acting b 2 -agonists to increase FE NO levels, probably by their effect on airway calibre and hence ventilated airway surface [115,46], but other studies could not confirm this [47]. While most studies did not find an effect of long acting b 2 -agonists (LABA) on FE NO , neither as monotherapy or added to ICS [116][117][118], one stuy did [119].…”
Section: Effects Of Asthma Treatment On Fe Nomentioning
confidence: 99%